The theoretical foundation of the emergence of catastrophic disasters in geosystems - Біланюк, В. І.; Петлін, В. М. (Man and Environment. Issues of Neoecology)
The article deals with real causes of natural disaster emergence and its manifestation in geosystems. We found, that despite long lasting researches of this issue, much progress in this field hasn’t been made. Any disaster in geosystem is, foremost, its development (qualitative change) that doesn’t evolve from the normal course of events on the certain level of geosystem’s organization. That is, this phenomenon is not controlled by combined geosystems and is not regular for them. In this case, we have not a sudden decrease of information within this part of landscape sphere, but abut chaotic, more precisely chaotic variability, significantly compressed in time. At the same time disasters are treated as integral parts of the evolution process, which is linked with macro evolutional actions, which in turn are not just simple of micro evolutional acts of stabilizing selection. Another word, disasters (both of natural and anthropogenic origin) in final result plays a roll of the certain impetus for activation not only regeneration processes but also for acceleration of evolutional processes in geosystems. As a consequence, a post-catastrophic mode emerges in geosystems, which characterizes the new state of inter-geosystem’s relations. Qualifying catastrophic phenomena as processes of qualitative development of geosystems, which is characterized by uncertain predictability and probability, allow us to treat them as those which have a variability of amplitudes that exceed the thresholds not only of real existing geosystems but also their ecological-functional environment. Therefore emergence of such disasters is associated with the concepts of chaos, uncertainty, disharmony, unpredictability etc. Despite the fact that the disaster is certainly linked to the mechanism of qualitative development of geosystems, the amplitude of change in geosystems in the catastrophic state goes beyond regular qualitative development. This inevitably leads to the emergence of instability in inter-geosystem post-catastrophic state. As a consequence to control the regenerative processes systems of higher level morphologically are involved - a kind of morphologically higher functional environment. As a result, the state of catastrophic instability transforms to quasi-balanced. In this case, several adjacent geosystems may also start qualitative development. The catastrophic phenomena in geosystems under the influence of anthropogenic factor may arise at any stage of its development even in very stable stage both in space and in time. The anthropogenic factor used ex- tremely powerful energy directed at the destruction of the regular functional structure of geosystems. As a consequence destruction of geosystem’s invariant starts within disaster zone, but also the emergence on their place spatial entities with extremely unstable attractors. Another type of anthropogenic-induced disasters is pushing disasters. This is a situation when a primordium of possible catastrophe already exists in the natural environment of geosystems or in geosystems per se. The human factor, in this case, is only able to "push" the situation to the disaster. This case requires much less energy. This pushing catastrophic situation can be understood as natural- anthropogenic. It is capable of being controlled by systems of a higher level of morphological organization. Catastrophic impact zone consists of a set of interrelated geosystems within which the impact of catastrophic phenomenon has significant differences. First of all, this is the core disaster area and its periphery. If the core area often suffers the most form catastrophic effects, the peripheral zone is characterized by considerable heterogeneity regarding catastrophic changes. The most intensive changes occur in the direction of the prevailing material and energy flows. That is even spreading of anthropogenic (technological) disaster spatially is controlled not so much by a human as by natural factors. Any zone of the catastrophic phenomenon is characterized by a zone of catastrophic processes – this is unstable, extremely energetic geophysical and geochemical entities of geosystems. Within them, the action of interrelated by processes of certain disaster is capable quantitatively or qualitatively change not only the parameters of geosystems but also their invariant, including geosystems of higher hierarchical levels of the organization, depending on the intensity of the action zone. This zone is characterized by catastrophic conceptual acuity that is within it a set of organizational patterns manifest themselves as a system in a state of aggravation. As a result of conceptual acuity manifests itself as tension patterns of action where their implementation time is reduced to a minimum. This facilitates the rapid involvement of geosystems at all levels of the hierarchical organization of all possible resources for localization of catastrophic phenomena in space and time and activation of the landscape areas regeneration processes at the affected site. Considered in the articles elements of geosystem theory of disasters are capable of widening considerably implementation on practice a common theory of disasters. Our study helps to make this theory more close to the real situation in the place. Namely, we suggest complementing already existing theory of disasters by geosystem module, which is much closer to reality in the natural environment.